Negotiation and Surrendering to Gender Inequalities in the Life Aspects of Same-Sex Couples - Worapitaksanond, Thanakorn (Journal of Multidisciplinary Academic Research and Development (JMARD), 2023)
This article studies negotiating and surrendering to gender inequalities in life aspects of same-sex couples. Documentary research was done with synthetic data gathered from gay, lesbian, bisexual, transgender, queer, intersex, and asexual (LGBTQIA+) couples in the Bangkok Metropolitan Area (BMA). Data was analyzed by queer gender performativity theory. Results were that 1) sexual knowledge developed from spontaneous sex classification in the dual system according to physiological gender through a gender biased neuroscientific system. Thus, physical sex was tied to a fixed masculine and feminine gender along with heterosexual norms, passing through a refinement process with social institutions pressuring alternative sexualities to be seen as abnormal and deviant. Sexuality tries to escape this pressure by creating diverse identities or flow to a point where sex is undefined, along with a feminist group challenging the original set knowledge to equalize female and male genders. These are key transitional points leading to the emergence of queers as representatives of an ideological movement and campaigning for civil liberties. 2) Marital life among male same-sex couples occurs after creation of a male identity of gay definition and sexual expression previously considered unstable. To achieve a lasting relationship despite fluctuations in sexual desire, gay couples seek stability by entering into a couple-building associations along heterosexual traditional guidelines. The roles of husband, wife, leader, and follower are predefined with relationships negotiated by constructing a socio-economic status with spousal tradition as an ideal family plan. To be accepted familially and societally, it is possible to live a married life, leading to legal requirements for marriage registration and gay paternity. 3) Constructing and coopting heterosexual love standards by gay groups, as well as seeing a right to stability in intimate life may be seen as virtual negotiations, may also involve surrendering structural power. This capitulation may also be part of the negotiation for stabilizing marital life and replacing negative expectations for gay couples with a socially optimistic lifestyle. However, all genders should be empowered to choose the right to live in a couple, whether heterosexual or not, and should be duly certified as such.